Traffic Data Collection for Floating Car Data Enhancement in V2I Networks. (25th July 2010) - Llorca, D. F.; Sotelo, M. A.; Sánchez, S.; Ocaña, M.; Rodríguez-Ascariz, J. M.; García-Garrido, M. A.
Abstract : This paper presents a complete vision-based vehicle detection system for floating car data (FCD) enhancement in the context of vehicular ad hoc networks (VANETs). Three cameras ( side-, forward- and rear- looking cameras) are installed onboard a vehicle in a fleet of public buses. Thus, a more representative local description of the traffic conditions (extended FCD) can be obtained. Specifically, the vision modules detect the number of vehicles contained in the local area of the host vehicle ( traffic load ) and their relative velocities. Absolute velocities ( average road speed ) and global positioning are obtained after combining the outputs provided by the vision modules with the data supplied by the CAN Bus and the GPS sensor. This information is transmitted by means of a GPRS/UMTS data connection to a central unit which merges the extended FCD in order to maintain an updated map of the traffic conditions ( traffic load and average road speed ). The presented experiments are promising in terms of detection performance and computational costs. However, significant effort is further necessary before deploying a system for large-scale real applications.